Sampling in der Musikproduktion Das Spannungsfeld zwischen Urheberrecht und Kreativität - Fischer, Georg (Büchner-Verlag, 2020)
20 years of dispute over one and a half seconds of copied music? The dispute in the »Metal on Metal« (German: »Metall auf Metall«) case between the music group Kraftwerk and the composer Moses Pelham even occupied the European Court of Justice in 2019. It shows that copyright has become a socially contentious issue that has pushed its way out of the niche of the artistic sphere and into the everyday lives of almost everyone. This process has not gone unnoticed by academia, and yet academia is only just beginning to understand the implications and effects of this copyright expansion in more detail. Sociologist Georg Fischer provides the first empirical study of sampling in music that explicitly examines the impact of German copyright law on creative practice. He shows the abundance and diversity of creative circumvention strategies that have spread and taken root in the shadow of copyright law - and with which artists necessarily limit their own visibility as well as the aesthetic complexity and monetary exploitation of their works.